1996
DOI: 10.1002/macp.1996.021971120
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic study of free‐radical copolymerization of butyl acrylate with methyl methacrylate in solution

Abstract: Free-radical copolymerization at 50°C of butyl acrylate with methyl methacrylate was carried out in benzene solution using 3 and 5 m o m as the overall concentration of monomers. Both the reactivity ratios and the rate coefficients of copolymerization are affected by the total monomer concentration. Reactivity ratios were analyzed on the basis of the "bootstrap" model, and the copolymerization rate is interpreted assuming a penultimate effect upon the propagation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 24 publications
3
61
1
Order By: Relevance
“…Thus, the values determined for k bb are composite numbers including the k tr,intra contribution. From a pure technical point of view, extremely high resolutions can be obtained, methods based on 13 C NMR spectroscopy can in principle distinguish between long and short chain branching 90 and thus provide access to separate values for k tr,intra and k bb . ).…”
Section: Chain-end Termination Rate Coefficient (Secondary Radicals)mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the values determined for k bb are composite numbers including the k tr,intra contribution. From a pure technical point of view, extremely high resolutions can be obtained, methods based on 13 C NMR spectroscopy can in principle distinguish between long and short chain branching 90 and thus provide access to separate values for k tr,intra and k bb . ).…”
Section: Chain-end Termination Rate Coefficient (Secondary Radicals)mentioning
confidence: 99%
“…2), have been observed frequently. [11][12][13][14][15] Varying explanations for this deviation from ideal polymerization kinetics were given due to the complex kinetic situation where numerous influences like the gel effect or the chain length dependency of bimolecular termination rate coefficient, k t , need to be considered. It is, however, noteworthy to add that ideal behavior is observed in dilute solution for methacrylates (and other monomers that propagate via a tertiary radical).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In effect, it is purported 4 • 5 that the observed value of the bimolecular termination rate constant k 1 (for homopolymerization) is in fact a weighted sum of the individual termination rate constants of each monomer involved in the reaction: where (8) Here w;* is the concentration of radicals of length i, D; is the rate coefficient for the diffusion of the chain end of a macroradical of length i, and Pspin and a are the spin probability that forbids a certain fraction of radical-radical encounters and a capture radius, respectively. At the risk of oversimplifying this analysis, what this means is that if the hypothesis that reactivity is independent of chain length is not entirely valid for the monomer in question, or there is a large disparity in chain lengths in the system, then the termination constant (and chain length ... ) will be diffusion controlled even in dilute solutions.…”
Section: Resultsmentioning
confidence: 99%
“…For different monomers, but in a similar system, Madruga and Fernandez-Garcia 8 showed that the reactivity ratios and rate constants of the system BuA-MMA (methyl methacrylate) varied as a function of the concentration of solvent (benzene). Semchikov et a/.…”
mentioning
confidence: 99%